The Religious Roots of Linguistic Nationalism - Kakridis, Yannis (The Historical Review/La Revue Historique, 2009)
This paper consists of two parts. In the first part, nationalism is analysed as a kind of gnostic religion (in the sense given to this term by E. Voegelin). In the mind of their adherents, nations are ultimate realities in which the objective (fatalistic) and the subjective (voluntaristic) side of the historical process coincide. In the second part, it is argued that language, by its dialectical character, appears as the very incarnation of the nationalist ideal. The ensuing paradoxes of nationalist language policy are listed and briefly analysed: the equation of the language of culture with the language of everyday life; the equation of norm with use; the equation of object language with metalanguage; the equation of modernity with authenticity; and the equation of the national with the universal.